ZA Batik web based ordering system / Noor Nadirah Hassan - Hassan, Noor Nadirah (2013)
The project is concentrated on implementing a web based ordering system to help a small-and-medium enterprise (SME) in batik industry in handling order of batik products from the customer. The limited opportunities to promote their products to the customer by using manual system have contributed the idea of implementation of a web based ordering system. Za Batik which can be categorized as a small-and-medium enterprise (SME) is located at Dungun, Terengganu. This organization has employed around 15 workers and currently, receives the design or customization of batik products from the customer in order to improve customer satisfaction. The aim of the research project is to help small-and-medium enterprise (SME) in promoting their products to the customer especially in the handicraft industry such as batik. This is because batik represents Malaysia’s identity. The project is developed by using agile methodology which consists of several phases such as define requirement or analysis, design, implementation, verifying or testing and lastly the result evaluation and analysis. The methodology is called agile since it is in an iterative development which can improve the quality of a website by injecting feedback from the customer. The feedback from the customer then is used to make an improvement from the limitations in the future. From the research, it is shown that by implementing a web based ordering system give a positive impact to the small-and-medium enterprise (SME) in conducting their business. However, there are some restrictions and limitations of this project and further research into tracking customer’s order status and put some button for selecting available size for batik product which offer various size such as blouse and men’s shirts is proposed.